Examining the connection between economic sectors, the unemployment rate and real GDP per capita – the case of EU countries - Peter Burger; Lea Šlampiaková (Cogent Economics & Finance)
This paper intends to bridge the gap in understanding the interaction between the sectoral division in the national economy, selected macroeconomic variables and innovation levels over time across EU countries. A comparative examination of theoretical knowledge in conjunction with an analysis of the empirical data was done. Descriptive statistics, cluster analysis and data mining were used to examine the data sets. Based on the results of the cluster analysis, the countries were divided into four clusters in each of the examined years. The results indicate a shift in the position of certain countries within the established clusters, reduction in the number of countries in both the elite and least performing clusters between 2010 and 2022 as well as an increase in the number of countries in the cluster with indicators most comparable to the average indicators of the EU27 countries. The countries within the elite cluster (except Malta) are distinguished by a significant percentage of the workforce engaged in the quaternary sector, elevated GDP per capita and pronounced degree of innovation performance. Conversely, the countries within the least efficient cluster exhibit a substantial share of people employed in the primary sector, relatively low GDP per capita and a low degree of innovative performance. This paper provides updated empirical insights into the changing economic dynamics and sectoral-macroeconomic connections within the EU. This highlights the alterations in economic and innovation patterns that can guide policymakers in formulating targeted interventions to optimize employment structures and improve competitiveness.